The Role of Probiotics in Treating Echinococcosis in Mice - Sheet, Arkan Saeed; Mohiemeed, Abdulkhaliq Alwan; Ali, Asmaa Abdulaziz (Iraqi Journal of Science, 2024)
This study investigated the role of probiotics in treating echinococcosis, considering three time periods (3, 5, and 7 months) and three bacterial dilutions. Mice were injected subperitoneally before and after primary infection with the rudiments. Before infection, the mice were injected with the Pro-30Max probiotics twice, with 48 hours interval. On the fifth day, they were infected with protoscoleces, and after 48 hours they were treated with the bacteria. The injections continued every 72 hours for all periods. A decrease in the number and weight of hydatid cysts was recorded reaching the value of 0.00 mg. Whereas a decrease in the weight of the liver and spleen and their inflation factors were recorded after 7, 5 and 3 months. The lowest weight of the liver and spleen reached 1.2869 and 0.196 grams, and their lowest inflation factors were 36.106 and 7.118, respectively, when treated with a dilution of 18 × 108 compared with the control group. At the same dilution, the percentage reduction of hydatid cysts increased after 7 months, reaching 100% compared with the control group.